2018
DOI: 10.1007/s13691-018-0330-5
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-colony-stimulating factor-producing metaplastic carcinoma of the breast with significant elevation of serum interleukin-17 and vascular endothelial growth factor levels

Abstract: Granulocyte-colony-stimulating factor (G-CSF) production in carcinomas is associated with a very aggressive phenotype. Interleukin (IL)-17 secreted from tumor-infiltrating lymphocytes induces the production of G-CSF and vascular endothelial growth factor (VEGF) in cancer tissue. We present a case of a G-CSF-producing metaplastic breast carcinoma (MpBC) accompanied by systemic elevation of IL-17 and VEGF levels. A 56-year-old woman presented with a rapidly growing tumor measuring > 10 cm in her left breast. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…We searched PubMed and Google Scholar using the keywords “G-CSF production” and “breast cancer”. As a result, there were only two well-reported cases of G-CSF-producing breast cancer [ 5 , 8 ]. According to Anano’s report, the diagnostic criteria for a G-CSF-producing tumor are extreme leukocytosis, elevated G-CSF activity, a decrease in the WBC count after tumor resection, and proof of G-CSF production in the tumor [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We searched PubMed and Google Scholar using the keywords “G-CSF production” and “breast cancer”. As a result, there were only two well-reported cases of G-CSF-producing breast cancer [ 5 , 8 ]. According to Anano’s report, the diagnostic criteria for a G-CSF-producing tumor are extreme leukocytosis, elevated G-CSF activity, a decrease in the WBC count after tumor resection, and proof of G-CSF production in the tumor [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…We treated a patient with G-CSF-producing malignant phyllodes tumor of the breast. It was a triple-negative type malignant tumor that was mainly composed of atypical stromal cells as in the past two reported cases [ 5 , 11 ]. Including this case, a G-CSF-producing tumor has presented as a malignant tumor mainly composed of stromal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient is currently alive without relapse at 30 months postoperative. breast cancer, including our case [1][2][3][4][5][6][7][8][9][10][11][12] (Table 1). Such tumors have a large proportion of special tissue type, and squamous cell carcinoma is a frequent type.…”
Section: Postoperative Coursementioning
confidence: 99%
“…Some studies have reported that serum G-cSF levels are significantly higher in breast cancer patients compared with healthy controls (48,(59)(60)(61)(62)(63). lawicki et al (60), demonstrated that the plasma levels of G-CSF and M-CSF were significantly increased in 54 breast cancer patients compared with in control group patients.…”
Section: G-csf Expression In Breast Cancermentioning
confidence: 99%